Effects of Deoxynivalenol-Contaminated Diets on Productive, Morphological, and Physiological Indicators in Broiler Chickens - Riahi, Insaf (Animals (Basel), 2020)
SIMPLE SUMMARY: The presence of mycotoxins in feed is a really significant problem worldwide; it leads to adverse effects on animals and great economic losses, especially in the monogastric industry. Deoxynivalenol (DON) is one of these mycotoxins that contaminates poultry feed and consequently has negative effects on this specie. Different concentrations of DON (5 and 15 mg/kg feed) were tested in broiler chickens. Results showed that high levels could adversely affect productive and welfare parameters; however, organ weights, morphological intestine indicators, and biochemical parameters were affected at low and high level of dietary DON. In general, even the low level of DON (5 mg/kg), which is the guidance level in complete poultry feed could affect the physiological status of birds. ABSTRACT: The present study with 1-day-old male broilers (Ross 308) was conducted to evaluate the effects of deoxynivalenol (DON) at different levels (5 and 15 mg/kg feed) on growth performance, relative weight of organs, morphology of the small intestine, serum biochemistry, and welfare parameters of broiler chickens. Forty-five broiler chicks were randomly divided into three different experimental groups with five replicates each: (1) control group received a non-contaminated diet, (2) contaminated diet with 5 mg DON/kg of feed, and (3) contaminated diet with 15 mg DON/kg of feed for 42 days. Results showed that feed artificially contaminated with DON at guidance level (5 mg/kg diet) did not affect growth performance parameters. However, 15 mg/kg reduced body weight gain and altered feed efficiency. DON at two assayed levels significantly increased the absolute and relative weight of thymus and the relative weight of gizzard and decreased the absolute and the relative weight of the colon. Compared to controls, both doses affected small intestine morphometry parameters. In terms of biochemical indicators, DON at 5 mg/kg reduced the creatine kinase level and at 15 mg/kg DON reduced the cholesterol level. Furthermore, DON at 15 mg/kg induced more fear in broilers compared to broilers fed the guidance level. It was concluded that even the guidance level of DON did not affect the chickens’ performance. However, its toxic effect occurred in some organs and biochemical parameters.